From Local Adaptation to Global Acceptance: Customer Engagement, Brand Loyalty, and Menu Localization - Oh Zi Jian; Rudresh Pandey; Nur Alya Maisarah Mazzuan; Aditya Kumar Sahu; Nur Amalina Hadirah Yusra; Nur Aqilah Abdul Halim; Nur Ardina Amir Hamzah; Sania Tomar; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2026)
This study examines strategic approaches for enhancing Marrybrown Malaysia’s global competitiveness through menu localization, customer engagement, and brand loyalty. Drawing on localization and engagement theories, the study investigates how customer engagement and brand loyalty influence acceptance of localized menu strategies in international markets. A quantitative research design was adopted, and data were collected from 151 Malaysian consumers using a structured questionnaire. Multiple regression analysis revealed that customer engagement has a significant positive effect on menu localization, while brand loyalty also demonstrates a positive but comparatively weaker influence. The findings suggest that active customer interaction and emotional attachment to the brand enhance consumer acceptance of culturally adapted menu offerings. This study contributes to the limited literature on Malaysian fast-food brands by providing empirical evidence on localization strategies that support global expansion. The findings offer managerial insights for Marrybrown to strengthen digital engagement and leverage loyal customers when implementing international localization strategies.